Do you Vape With Aloha?: How culture and place are used to spread misinformation on Instagram. (30th September 2020) - Sentell, T; Kearney, M; Hazen, A; Dela Cruz, M R; Yamauchi, J; McHenry, L; Rodericks, B; Massey, P
Abstract: Background: Forty-two percent of high school teens in Hawai'i have tried e-cigarettes, double the United States' national average. Native Hawaiians have higher use than other racial/ethnic groups. While Hawai'i state law prohibits tobacco sales to anyone under 21, many Hawai'i adolescents purchase e-cigarettes on the internet, often through social media. Methods: We collected 717 public Instagram posts from April and December 2018 geotagged in Hawai'i that mentioned one or more hashtag search terms (e.g., #vape, #ecig). All relevant, working posts (n = 476) were manually coded for text and image characteristics. Results: Over 80% of posts were from vape shops (n = 389 of 476;81.7%). Caption text commonly mentioned brand names (n = 409;85.9%), vape shop names (n = 379;79.6%), and flavors (n = 103;21.6%). The most frequent image elements were logos (n = 395;82.7%), e-cigarettes (n = 324;68.1%), and flavors (n = 110;23.1%). Less than one in 50 (n = 9;1.8%) included caption text warnings. One in five posts (n = 94, 19.7%%) featured content specific to Hawai'i including references to Native Hawaiian culture, flavors and foods, scenery, plants, animals, and language. For example, "Hawai'i Nei...Stay Blessed n Vape With Aloha" or "Ma'o Hau Hele" is the state flower of Hawaii, combined with a refreshing sweet raspberry it makes the perfect balance of flavor." User engagement (i.e., likes) varied, with a median of 17 likes per post (range: 0-308). Posts with Hawaiian cultural elements received significantly more likes than other posts (median: 22 versus 16;p=0.0047). Conclusions: Culture is a critical strength that can support positive health outcomes in many communities. Vape shops and product promoters explicitly misappropriated Native Hawaiian culture to sell e-cigarettes on Instagram, while downplaying known harms. Adolescents and young adults may be particularly vulnerable given social media's role as a powerful health behavior influence and an e-cigarette purchasing source. Key messages: Health misinformation is contextualized within culture and place in a way that is compelling to users, may put youth at particular risk, and can perpetuate health disparities. Our study supports tailored health campaigns and interventions for local communities and cultures to combat such online misinformation.